Porphyrins as Colorimetric and Photometric Biosensors in Modern Bioanalytical Systems. (30th March 2020) - Norvaiša, Karolis; Kielmann, Marc; Senge, Mathias O.
Abstract: Advances in porphyrin chemistry have provided novel materials and exciting technologies for bioanalysis such as colorimetric sensor array (CSA), photo‐electrochemical (PEC) biosensing, and nanocomposites as peroxidase mimetics for glucose detection. This review highlights selected recent advances in the construction of supramolecular assemblies based on the porphyrin macrocycle that provide recognition of various biologically important entities through the unique porphyrin properties associated with colorimetry, spectrophotometry, and photo‐electrochemistry. Abstract : From the simple colorimetric detection of physiological pH range to complex DNA strand analysis ‐ the versatility of the macrocyclic system and a plenitude of chemical modifications have allowed the production of a plethora of sensitive and selective porphyrin‐based bioreceptors. In this review, we discuss recent advances in modern porphyrin‐based bioanalytical systems in the fields of colorimetry, spectrophotometry and photo‐electrochemistry.